Alterações pulmonares funcionais e radiológicas decorrentes da radioterapia no tratamento do câncer de mama - Renata de Carvalho Schettino (2015)
Breast cancer is the most common and the leading cause of cancer death among women in Brazil and worldwide. Radiation therapy to the breast and regional lymph nodes is commonly used in the treatment of breast cancer. Pulmonary changes resulting from radiation therapy are clinically asymptomatic in most patients and often underdiagnosed. The objective of this study was to evaluate and correlate the pulmonary changes caused by radiotherapy in the treatment of breast cancer by means of instruments and routine and use imaging tests. Participated in this prospective study 41 women diagnosed with breast cancer and data collection were performed, during 2008 to 2010 at Hospital das Clínicas – UFMG, before, after and monthly up to six months after radiotherapy. Radiographs were taken before radiotherapy, one month and six months after radiotherapy. Respiratory capacity measures were evaluated (inspiratory capacity and forced vital capacity), respiratory muscle strength, peak expiratory flow, six-minute walk test and conventional chest X-rays. It was observed that the distance covered on the six-minute walk test has direct association with the muscular strength measurements and the Borg dyspnea index to have an inverse association with the maximal expiratory pressure and peak expiratory flow. In addition, the Borg dyspnoea and for the distance were significantly associated with radiographic findings. The maximal inspiratory pressure showed a significant reduction in the periods immediately after radiotherapy and in the first post-radiotherapy and patients undergoing adjuvant chemotherapy month showed expiratory flow peak values significantly lower than those observed for the neoadjuvant group in pre-and post-radiotherapy periods radiotherapy. Women undergoing radiation therapy in the treatment of breast cancer have reduced maximal inspiratory pressure in the first post-radiotherapy month and peak expiratory flow is a lung variable that is not influenced radiotherapy. The functional capacity measured by six-minute walk test is associated with pulmonary variables and pulmonary changes found in chest radiographs of women undergoing radiotherapy for breast cancer.